Management of Fusarium wilt of tomato under protected conditions using Brassica crop residues, AM fungi and biocontrol agents - JITENDER SHARMA, NARENDER K. BHARAT* and (Indian Phytopathology, 2015)
Fusarium wilt of tomato was managed using three fungal, viz. Trichoderma viride, T. hamatum, T. harzianum and a bacterial viz. Pseudomonas fluorescens biocontrol agents in vitro. Four different genera of arbuscular-mycorrhizal (AM) fungi viz., Glomus sp., Acaulospora sp., Scutellospora sp. and Gigaspora sp. were isolated from tomato soil and their culture consortium was multiplied on Guinea grass in pots. Under in vitro condition, T. viride was found most effective in inhibiting the mycelial growth of F. o. lycopersici. Amongst different bio-fumigant crop residues (fresh as well as dry) tested in vitro, taramira showed highest inhibition in mycelial growth of F. o. lycopersici i.e. 62.59 and 60.74 per cent, respectively. All the effective management inputs evaluated under in vitro conditions were again evaluated under polyhouse in an integrated manner. The results of polyhouse experiment indicated that bio-fumigation of sick soil with taramira crop residues for 30 days, and application of formulation of T. viride along with FYM and inoculation of transplants with indigenous AM fungi resulted in to more than 80% control of Fusarium wilt of tomato under polyhouse conditions. This practice also increased the growth viz., height, number of branches and plant dry weight as well as yield parameters like number of fruits per plant and fruit yield per plot. Colony forming units (cfu/g) of Fusarium sp. were decreased while that of Trichoderma sp. increased in soil owing to treatment of soil with bioinoculants. The spore population of AM fungi was found more in the plots receiving this treatment as compared to control.